Analysis of mathematical models for calculating following intervals in main flows the prevailing road conditions in the Russian Federation - A. Yu. Mikhailov; E. L. Popova (Вестник СибАДИ)
Introduction. This paper presents the results of a study on the methods for calculating the capacity of level crossings. The purpose of writing this research paper is determine the best methodology for calculating the intervals in the main flows for the prevailing road conditions in the Russian Federation, that a new methodology to calculate capacity adapted to domestic road conditions would be developed in the future.Materials and methods. In recent decades of market relations in the Russian Federation, one can note a rapid increase in motorization in human settlements. The number in 550 vehicles per 1000 people in domestic entities is expected to have been increasde by 2025, which is significantly higher than the current level in European part of the Russian Federation. It is important to note that when the number of vehiclec is increasing, which level is about 80%, it is essential to increase road crossings capacity. Results. At the moment the methodology for calculating capacity and queue length is the same. It should be noted that the current models are not properly described in the domestic studies, but the calculations were made using models developed in the 1960s and 1970s.